Respuesta :
Answer:
[tex]f^{-1}(x)=-\frac{1}{5}(x+4)[/tex]
Step-by-step explanation:
The given function is [tex]f(x)=-5x-4[/tex]
Substitute y = f(x)
[tex]y=-5x-4[/tex]
Interchange x and y
[tex]x=-5y-4[/tex]
Solve for y
[tex]x+4=-5y\\\\y=-\frac{1}{5}(x+4)[/tex]
This is nothing but the inverse of the function. Hence,
[tex]f^{-1}(x)=-\frac{1}{5}(x+4)[/tex]
The inverse of the function is [tex]f^{-1}(x)=-\frac{1}{5}(x+4)[/tex]
Functions are written in terms of variable. The inverse of the function f(x) = –5x – 4 is y = (x + 4)/-5
How to find the inverse of a function?
Functions are written in terms of variable. Given the function as shown:
f(x) = –5x – 4
This can be written as
y = –5x – 4
Replace y with x
x = -5y - 4
Make y the subject of the formula
-5y = x + 4
y = (x + 4)/-5
Hence the inverse of the function f(x) = –5x – 4 is y = (x + 4)/-5
Learn more on inverse of a function here: https://brainly.com/question/2873333
#SPJ2